HUBUNGAN TINGGI MUKA AIR DAN DEBIT ALIRAN SUNGAI KARANG MUMUS DI LOKASI DESA PAMPANG KOTA SAMARINDA - Wiadnyana, Dewa Made; Subagiada, Kadek; Natalisanto, Adrianus Inu (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2019)
Karang Mumus River Pampang Village Samarinda City has a postal system in accordance with what is needed to overcome or overcome problems related to the environment. This research was carried out around the Pampang River in Samarinda City which was at coordinates 117 ° 06 '44 .00